Effect Of Vitamine AND Selenum On Immune Response Of CO — Baghdad Vaccine In Sheep.‎ - M.H.AL-Judi, A.; H.Hameed, R.; D.Salman, A. (The Iraqi Journal of Veterinary Medicine, 2004)
This study was done on 57 Awassi pregnant ewes, divided in to 5 groups, the Ist control group, the second group received twicel.M.injections of vitamin E (900 mg) and Selenium (3mg), the third group received one injection of vitamin E (900mg) and selenium (3 mg), the fourth group received vitamin E via feed block (1 gm) daily for two weeks, the fifth group received vitamin E via feed block for one week (1gm daily), and all groups injected with C Baghdad vaccine.This study had been shown a significant difference in antibody titer between treated groups and the control group, from2weeks post vaccination There were significant difference in antibody _ titre (p<0.05) between lambs of treated and control group. While there were no significant difference in body weight of ewes and lambs, but was a significant difference in milk production of treated and control group.